Comparative Mitogenomic Analysis and the Evolution of Rhizoctonia solani Anastomosis Groups - Lin, Runmao; Xia, Yuan; Liu, Yao; Zhang, Danhua; Xiang, Xing; Niu, Xianyu; Jiang, Linjia; Wang, Xiaolin; Zheng, Aiping (Frontiers in Microbiology, 2021)
Mitochondria are the major energy source for cell functions. However, for the plant fungal pathogens, mitogenome variations and their roles during the host infection processes remain largely unknown. R. solani, an important soil-borne pathogen, forms different anastomosis groups (AGs) and adapts to a broad range of hosts in nature. Here, we reported three complete mitogenomes of AG1-IA RSIA1, AG1-IB RSIB1, and AG1-IC, and performed a comparative analysis with nine published Rhizoctonia mitogenomes (AG1-IA XN, AG1-IB 7/3/14, AG3, AG4, and five Rhizoctonia sp. mitogenomes). These mitogenomes encoded 15 typical proteins (cox1-3, cob, atp6, atp8-9, nad1-6, nad4L, and rps3) and several LAGLIDADG/GIY-YIG endonucleases with sizes ranging from 109,017 bp (Rhizoctonia sp. SM) to 235,849 bp (AG3). We found that their large sizes were mainly contributed by repeat sequences and genes encoding endonucleases. We identified the complete sequence of the rps3 gene in 10 Rhizoctonia mitogenomes, which contained 14 positively selected sites. Moreover, we inferred a robust maximum-likelihood phylogeny of 32 Basidiomycota mitogenomes, representing that seven R. solani and other five Rhizoctonia sp. lineages formed two parallel branches in Agaricomycotina. The comparative analysis showed that mitogenomes of Basidiomycota pathogens had high GC content and mitogenomes of R. solani had high repeat content. Compared to other strains, the AG1-IC strain had low substitution rates, which may affect its mitochondrial phylogenetic placement in the R. solani clade. Additionally, with the published RNA-seq data, we investigated gene expression patterns from different AGs during host infection stages. The expressed genes from AG1-IA (host: rice) and AG3 (host: potato) mainly formed four groups by k-mean partitioning analysis. However, conserved genes represented varied expression patterns, and only the patterns of rps3-nad2 and nad1-m3g18/mag28 (an LAGLIDADG endonuclease) were conserved in AG1-IA and AG3 as shown by the correlation coefficient analysis, suggesting regulation of gene repertoires adapting to infect varied hosts. The results of variations in mitogenome characteristics and the gene substitution rates and expression patterns may provide insights into the evolution of R. solani mitogenomes.